Research status and progress of hydrogen embrittlement of hydrogen pipelines - Jianwei DU; Hongliang MING; Jianqiu WANG (You-qi chuyun)
Hydrogen transportation through pipelines has extremely high economic value in realizing the development of the hydrogen energy industry and promoting efficient energy utilization. It is an important link to accelerate the realization of the energy transformation strategy. The evaluation of the compatibility of hydrogen with steel pipelines is the premise of the safe application of hydrogen transportation through pipelines. The hydrogen embrittlement caused by hydrogen entering the material has brought great challenges to safe hydrogen transportation through pipelines. However, no consensus has been formed regarding the mechanism of hydrogen embrittlement, and no effective protection method is available against hydrogen embrittlement. The study on hydrogen embrittlement of steel pipeline materials intuitively exhibits the mechanical property change law caused by hydrogen entering the material, which is of great significance in mechanism research and engineering application. Herein, the research status of hydrogen embrittlement in hydrogen pipelines was summarized from the aspects of materials for hydrogen pipelines, mechanism of hydrogen embrittlement, research methods of hydrogen embrittlement and its influencing factors. Besides, their influence on hydrogen embrittlement behavior in the materials for hydrogen pipelines was elaborated in view of the experimental methods, conditions and material microstructure. In addition, the rationality of current experimental methods and results were discussed, and the research directions to be concerned in future work were put forward.